Correlation of Oceanographic Parameters with Yellowfin Tuna Catch in Fisheries Management Areas (WPP) 573 and 713 - Sativa, Denianto Yoga; Muhammad Maulana Aldian Putra; Ida Ayu Ketut Marini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Oceanographic parameters are related to the distribution of fish in the waters. The purpose of this study was to analyze the distribution trends of sea surface temperature (SST) and chlorophyll-a (CHL) and to determine the spatial-temporal correlation with the catch of yellowfin tuna. This research took place in WPP 573 and 713 between the north and south of the Alas Strait. Remote sensing methods and statistical regression analysis for SST and CHL in 2023 over 12 months. The penetration results of Aqua MODIS in 2023 show the highest fluctuation SST trend in December (30.71°C), the lowest in August (27.3°C). The highest CHL distribution occurred in December (37.81 mg/m3), and the lowest in February (0.66 mg/m3). The results of linear regression analysis between SSTs; CHL; SST and CHL, for yellowfin tuna fishing, obtained a correlation coefficient (r) of 0.421 each; 0,476; 0.623. Conclusions: 1). The relationship between SST and CHL with yellowfin tuna is in the strong category; 2). The fluctuating catch of yellowfin tuna causes the CHL and SST trends to change every month. CHL and SST values were highest in December, but they did not have a major effect on catches.